Influence of Product Diversification on Financial Performance of Microfinance Institutions in Nairobi County, Kenya. - James, Margaret Wanja; Rintari, Nancy; Muema, Wilson (International Journal of Finance, 2023)
Purpose: To examine the influence of product diversification on financial performance of microfinance institutions in Nairobi County, Kenya. Methodology: The study applied descriptive research design during the collection of data. The study's target population was 14 microfinance banks. The sample size was selected using simple random sampling method after determination using Kothari (2004) sampling formular to obtain 19 operations managers, 34 tellers, 40 credit officers, and 28 customer care officers. The study collected primary and secondary data. The study conducted a pre-test study of the questionnaires in Cooperative bank and I&M banks in Nairobi County. Further, the study tested reliability and validity. Further, quantitative data was analyzed using SPSS software version 25 to generate descriptive and inferential statistics. The various descriptive analysis was frequencies, percentage and mean, while linear and multiple regression analysis was done as part of inferential statistics analysis. Results: The questionnaire results disclosed that 87(89%) strongly agreed and 9(9%) agreed (mean of 4.83) that there were efforts from the management to allow the existence of different types of loan products with various requirements. Nevertheless, 21(21%) strongly disagreed and 19(20%) disagreed (mean of 2.92) that the staff were always encouraged to offer suggestions to the management on how products could be improved further to incorporate the needs of each customer. Additionally, under model summary, R was 0.746 and R-square was .557 at a Durbin-Watson value of 1.442. Further, the significance coefficient of ANOVA was 0.001 hence less than 0.05. The results therefore enabled the study reject the null hypothesis. Unique contribution to theory, policy and practice: The conclusions made on product diversification was that the management failed to incorporate various improvement suggestions made on the different implemented products. The issues gave a major reason why MFIs revenue was declining in Kenya. That is, in as much as they had different products, the specific client needs were not being met and if they were met, it was very expensive to maintain the products. The study recommends that the management of MFIs should commission a special committee of expert to review the requirement of each and every product being offered.